Speech acts and speaker intention in the case concerning sovereignty over the islands of Sipadan and Ligitan - Burhanudeen, Hafiza (Journal of Modern Languages, 2017)
Language is frequently used as a persuasive tool among countries as a dispute resolution mechanism either through diplomatic negotiation or through arbitration or adjudication mechanisms such as the International Court of Justice in The Hague, The Netherlands. Inherent within language are a myriad of speech acts designed to convey either implicitly or explicitly the communicative intent of the speakers involved. This paper seeks to highlight speaker intention via the kinds of speech acts used in the language of Counsels representing Malaysia and Indonesia in the case concerning sovereignty over the two islands of Sipadan and Ligitan on June 3-12, 2002 at the International Court of Justice. Data for this paper is extracted primarily from the verbatim records of Sir Elihu Lauterpacht, Q.C., C.B.E. lead Counsel for Malaysia and Sir Arthur Watts, Q.C. Counsel for the Republic of Indonesia.